Exercise testing‐based algorithms to diagnose McArdle disease and MAD defects. (10th May 2018) - Noury, J.‐B.; Zagnoli, F.; Carré, J.‐L.; Drouillard, I.; Petit, F.; Le Maréchal, C.; Marcorelles, P.; Rannou, F.
Abstract : Objective: As exercise intolerance and exercise‐induced myalgia are commonly encountered in metabolic myopathies, functional screening tests are commonly used during the diagnostic work‐up. Our objective was to evaluate the accuracy of isometric handgrip test (IHT) and progressive cycle ergometer test (PCET) to identify McArdle disease and myoadenylate deaminase (MAD) deficiency and to propose diagnostic algorithms using exercise‐induced lactate and ammonia variations. Methods: A prospective sample of 46 patients underwent an IHT and a PCET as part of their exercise‐induced myalgia and intolerance evaluation. The two diagnostics tests were compared against the results of muscle biopsy and/or the presence of mutations in PYGM . A total of 6 patients had McArdle disease, 5 a complete MAD deficiency (MAD absent), 12 a partial MAD deficiency, and 23 patients had normal muscle biopsy and acylcarnitine profile (disease control). Results: The two functional tests could diagnose all McArdle patients with statistical significance, combining a low lactate variation (IHT: <1 mmol/L, AUC = 0.963, P  < .0001; PCET: <1 mmol/L, AUC = 0.990, P  < .0001) and a large ammonia variation (IHT: >100 μmol/L, AUC = 0.944, P  = .0005; PCET: >20 μmol/L, AUC = 1). PCET was superior to IHT for MAD absent diagnosis, combining very low ammonia variation (<10 μmol/L, AUC = 0.910, P  < .0001) and moderate lactate variation (>1 mmol/L). Conclusions: PCET‐based decision tree was more accurate than IHT, with respective generalized squared correlations of 0.796 vs 0.668. IHT and PCET are both interesting diagnostic tools to identify McArdle disease, whereas cycle ergometer exercise is more efficient to diagnose complete MAD deficiency.